2006
DOI: 10.3129/i06-074
|View full text |Cite
|
Sign up to set email alerts
|

Optic neuropathy in refractory neurosarcoidosis treated with TNF-α antagonist

Abstract: Corticosteroids alone and with immunosuppressive agents failed to suppress the active disease. Alternative therapy of infliximab perfusions resulted in disease remission and relative visual improvement, and this treatment may warrant further clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Although there have been no comparative trials between the biologic agents for sarcoidosis, infliximab is the most heavily reported medication in the literature [611], and overall has shown great promise in the treatment of sarcoidosis patients refractory to more conventional therapies [6, 7, 12, 26]. Favorable outcomes of infliximab therapy in patients who have renal sarcoidosis [13], vertebral sarcoidosis [14], joint sarcoidosis [15], optic neuropathy [16], pulmonary sarcoidosis [6, 17], retinal vasculitis [18], cutaneous sarcoidosis [35, 22], neurosarcoidosis [19], and cardiac sarcoidosis [20] have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been no comparative trials between the biologic agents for sarcoidosis, infliximab is the most heavily reported medication in the literature [611], and overall has shown great promise in the treatment of sarcoidosis patients refractory to more conventional therapies [6, 7, 12, 26]. Favorable outcomes of infliximab therapy in patients who have renal sarcoidosis [13], vertebral sarcoidosis [14], joint sarcoidosis [15], optic neuropathy [16], pulmonary sarcoidosis [6, 17], retinal vasculitis [18], cutaneous sarcoidosis [35, 22], neurosarcoidosis [19], and cardiac sarcoidosis [20] have also been reported.…”
Section: Discussionmentioning
confidence: 99%